Influence of Tax Avoidance and Tax Risk on Firm Risk with Independent Commissioners as Moderators - Wahyu Tri Ardiantoro; Siti Mutmainah (DIPONEGORO UNIVERSITY, 2025)
This study aims to analyze the effect of tax avoidance and tax risk on firm risk, and to analyze the role of independent commissioners as moderating variable in this relationship. This study uses quantitative methods with secondary data obtained from the annual financial statements of companies in sectors the industrial goods, industrial services, and multi-sector holdings those listed on the Indonesia Stock Exchange in 2021-2023. Data analysis in this study was carried out using multiple linear regression. The results showed that tax avoidance calculated using ETR has no effect on firm risk calculated using the stock return volatility. Meanwhile, tax risk calculated using the volatility of ETR has a negative influence on firm risk. On the other hand, independent commissioners calculated using the proportion of independent commissioners in the board of commissioners have no moderating effect on the relationship between tax avoidance and tax risk on firm risk.